Delphinium as a model for development and evolution of complex zygomorphic flowers - Sharma, Bharti; Pandher, Mankirat Kaur; Alcaraz Echeveste, Ana Quetzali; Romo, Rene Kenny; Bravo, Marianellie (Frontiers in Plant Science, 2024)
The complex zygomorphic flowers of the early-diverging eudicot Delphinium provide an opportunity to explore intriguing evolutionary, developmental, and genetic questions. The dorsal perianth organs, consisting of a spurred sepal and the nectar-bearing spurred petal(s) in Delphinium, contribute to the dorso-ventralization and zygomorphic flower morphology. The seamless integration of the two or three dorsal petaloid spurred organs is considered a synorganization, and the resulting organ complex is referred to as a hyperorgan. The hyperorgan shows variability within the tribe due to variation in the number, size, and shape of the spurs. Research in recent decades within this tribe has enhanced our understanding of flower morphological evolution. More recently, functional studies using the RNAi approach of Virus-Induced Gene Silencing (VIGS) have unraveled interesting results highlighting the role of gene duplication in the functional diversification of organ identity and symmetry genes. Research in this early-diverging eudicot genus bridges the gaps in understanding the morphological innovations that are mostly studied in model grass and core eudicot clades. This first comprehensive review synthesizes eco-evo-devo research on Delphinium, developing a holistic understanding of recent advancements and establishing the genus as an exceptional model for addressing fundamental questions in developmental genetics, particularly in the evolution of complex flowers. This progress highlights Delphinium's significant potential for future studies in this field.